Creatinine clearnce Rate (CCR) in Dignosing Different stages of chronic kidney Disease (CKD) - An update and review - Alam, MM Jahangir; Chowdhury, Fasle Rabbi; Chowdhury, Faizul Islam; Saha, Anup Kumar; Hoque, AKM Aminul; Mujiburrahman, Md (Journal of Medicine, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI = 10.3329/jom.v7i2.1367 J MEDICINE 2006; 7 : 64-69